2020
DOI: 10.2147/amep.s276221
|View full text |Cite
|
Sign up to set email alerts
|

<p>Student Perception of Microbiology Laboratory Skills Learning Through a Problem-Based Learning Curriculum: Arabian Gulf University Experience</p>

Abstract: Introduction The curriculum at medical school at Arabian Gulf University is centered on small group learning and real-life problems provided to students and guiding students to learn actively. In microbiology, laboratory skills are taught in an innovative manner using mini cases and different lab sessions and are integrated with other basic sciences. This article describes the format and pattern of laboratory skills sessions conducted using PBL methods at Arabian Gulf University and discusses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…is narrows the opportunity and freedom that should be afforded to students in trying out their inquiry techniques, where they make errors, learn from those errors, and make learning more interesting and permanent [6]. Students are guided and trained to think critically about a problem with team members and arrive at reliable solutions [1]; if students are allowed to manipulate equipment and materials as a result, they will learn more. He also claimed that in order for laboratory activities to be meaningful, students must be given the opportunity to reflect on findings, clarify understanding and misunderstanding with peers, and use available resources.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…is narrows the opportunity and freedom that should be afforded to students in trying out their inquiry techniques, where they make errors, learn from those errors, and make learning more interesting and permanent [6]. Students are guided and trained to think critically about a problem with team members and arrive at reliable solutions [1]; if students are allowed to manipulate equipment and materials as a result, they will learn more. He also claimed that in order for laboratory activities to be meaningful, students must be given the opportunity to reflect on findings, clarify understanding and misunderstanding with peers, and use available resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to existing literature, one of the inputs for a high-quality education is the use of laboratory activities [1], which are common elements of scientific instruction at all levels of education. Nowadays, there is a global change in teaching and learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…Bindayna surveyed the effectiveness of the PBL microbiology practice module on a small group of 110 students at the Faculty of Medicine, Arabian Gulf University, Bahrain, and found that more than 50% of the students agreed or strongly agree that the time spent on PBL is moderate, the topics discussed are relevant, the lecturer's presentations are clear, the pre-sessional tutorials are brief and supportive of the learning. Only 38% of students thought that the lectures were lengthy [3].…”
Section: Comparison Between the Two Groups Of Students' Satisfaction ...mentioning
confidence: 99%
“…The use of PBL in a laboratory setting promotes active learning. In fact, when combined with case-based scenarios, practice sessions enhance student understanding and help improve student outcomes [3].…”
Section: Comparison Between the Two Groups Of Students' Satisfaction ...mentioning
confidence: 99%
See 1 more Smart Citation